Women in sustainability research: Examining gender authorship differences in peer-reviewed publications - Barreiro-Gen, Maria; Bautista-Puig, Núria (Frontiers in Sustainability, 2022)
Higher Education Institutions (HEIs) have been undertaking considerable efforts to embed sustainability into their system; however, there has been limited studies on the incorporation of sustainability in research. In parallel, it has been found that women have an important role in contributing to sustainability, since they are more engaged and have a more holistic perspective of sustainability than men. These two phenomena have resulted in limited studies about the contribution of women to sustainability research (i.e. in scientific publishing). A bibliometric analysis of over 39,000 documents (with 147,090 authorships) was done with the aim of filling this gap, focusing on sustainability peer-review publications in Europe between 2015 and 2020. The results show that women presence in sustainability research has been increasing during the last years; however, there are still few female authorship publications, even in fields that have been traditionally women-oriented; in addition their publications have been less recognised by the scientific community. The results also show substantial gender differences in terms of author leadership, where female senior researchers are more likely to mentor female junior researchers than men. Female researchers tend to collaborate nationally, but they could improve their international collaboration since this can improve their research and impact. More support should be provided to women researchers to help fostering women’s sustainability engagement and holistic perspectives, to reduce existing negative feedback loops and increase positive ones. Achieving gender equality is sine qua non in achieving sustainable societies.